Analisis Interaksi Obat Secara Farmakokinetik dan Farmakodinamik Terhadap Pasien Nefropati Diabetik di Rumah Sakit X Kota Jambi Tahun 2022 - Farah, Zahratul; Sutrisno, Deny; Mitra, Aisa Dinda (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Diabetic nephropathy (ND) is a complication of diabetes in the kidney. Nephropathy, or kidney disease, is the leading cause of death and disability in diabetes. The first clinical manifestation of diabetic nephropathy is microalbuminuria. If a patient is diagnosed with microalbuminuria, the development of end-stage renal and cardiovascular disease can be prevented by controlling blood pressure, glucose, and lipids. This study aimed to determine pharmacokinetic and pharmacodynamic drug interactions, determine drug interactions and severity in patients, determine the relationship between age and drug severity and gender relationship with drug severity in patients with diabetic nephropathy at X Hospital Jambi City in 2022. The method used in this research is descriptive method. The data collected in this study came from the medical records of diabetic nephropathy patients at X Hospital Jambi City in 2022. The total population in this study was 67 patients with a total sample of 46 patients. The results showed that the highest prevalence in the sample was female (56.52%), elderly patients aged 46-55 years (47.83%), drugs that interact with lantus ËƒË‚ novorapid (8.43%), patients experiencing drug interactions (71.74%), pharmacodynamic interactions (92.77%), pharmacokinetic interactions (4.82%), minor (10.84%), moderate (78.31%), and major severity (10.84%). The conclusions drawn from this study were based on the interaction mechanism, namely there were 6 cases (7.23%) of pharmacokinetic interactions and 77 cases of pharmacodynamic interactions (92.77%). Based on interactions with 9 cases of minor severity (10.84%), 65 cases of moderate severity (78.31%), and 9 cases of major severity (10.84%). And there is no relationship between the severity of the drug and age and gender.